Housing Market Fundamentals, Housing Quality and Energy Consumption: Evidence from Germany - Marius Claudy; Claus Michelsen (The Energy Journal, 2016)
This study investigates the relationship between regional housing market fundamentals and energy consumption. We argue that dwellings, in particularly rental properties, are not only consumer goods, but also constitute financial market assets. Properties are spatially fixed and traded in regional contexts, where real estate market characteristics like vacancy, income levels, and expectations determine rent and prices, which in turn provide incentives to invest in housing quality. The level of housing quality (e.g. windows, building materials, or heating technology) in turn influences the level of energy consumption. While this view is established in the real estate and urban economics literature, it has only recently found its way into the energy debate. As a result, the relationship between regional housing market fundamentals and energy consumption has received little attention. This study provides a first attempt to address this paucity. Utilizing aggregate data on regional space-heating energy consumption from over 300,000 apartment buildings in 97 German planning regions, the study applies structural equation modeling to estimate the influence of housing market fundamentals on the level housing quality, and subsequently on regional energy consumption. Findings provide first evidence that regional differences in housing market conditions have a significant impact on housing quality and energy consumption. Specifically, the results suggest that carbon abatement programs in buildings should focus on regions with weak housing market fundamentals, as market incentives are unlikely to incentivize investors to invest in housing quality attributes. The authors conclude by highlighting important implications for energy research and avenues for further investigations.
Keywords: Q41; Q42; Q21; Q24; 330; heating energy demand; energy efficiency gap; regional housing